PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA PERUSAHAAN PADA PT TRANS MARGA JATENG - Widyanita, Fithri; Ilham, Ratih Milati (LPPM Universitas Bina Bangsa, 2023)
One type information system used by organizations is an accounting information system (AIS). AIS is an integral part of the company’s information system used to manage day to day operations and generate accounting information needed by management and stakeholders. The information produced by AIS is used for decision-making and policy making within the company. AIS also plays a crucial role in improving overall company performance. With the help of AIS, companies can monitor and measure their performance through the measurement of various activities within the company chain. The population in this study consisted of 34 employees, including 10 structural employess and 24 functional employess at PT Trans Marga Jateng. The sampling method used was purposive sampling, and the statistical tool used was multiple linier regression analysis. The results of the study proved that the accounting information system has an influence on company performance